2016
DOI: 10.4103/0976-3147.181488
|View full text |Cite
|
Sign up to set email alerts
|

A community-based case–control study of prevalence and pattern of cognitive impairments in patients with epilepsy residing in South-Eastern Nigeria

Abstract: Background:Epilepsy is the commonest neurological disorder encountered in Sub-Saharan Africa. The quality of life of patients with epilepsy (PWEs) is adversely affected by cognitive impairments.Aim:This study investigated the prevalence and pattern of cognitive impairments in PWE in Ukpo community located in a South-Eastern state in Nigeria using Community Screening Interview for Dementia (CSID) and a computer-assisted cognitive test battery (FePsy).Methods and Patients:Fifty-one PWEs were studied and compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Cognitive impairment is a frequently encountered but neglected problem in epilepsy [2,3,10,13]. To the best of our knowledge, this is the first study to systematically assess cognitive function of PWE in an onchocerciasis-endemic area in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Cognitive impairment is a frequently encountered but neglected problem in epilepsy [2,3,10,13]. To the best of our knowledge, this is the first study to systematically assess cognitive function of PWE in an onchocerciasis-endemic area in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 96%
“…The prevalence of cognitive impairment in the adult population in sSA is estimated at 6.3% [47]. Studies in South Eastern Nigeria in 2016 [3] and in Taiwan in 2005 [48] reported prevalence values of 19.6% and 36% respectively of cognitive impairment in PWE. Another study of cognitive impairment in sub group of epilepsy patients living in an onchocerciasis endemic region in Democratic republic of Congo and specifically presenting nodding seizures revealed a prevalence of 71.9% [49].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations